The Use of Varied Media in Learning to Analyze the Content and Language of Drama Texts - Nurain Nggilu; Sayama Malabar; Puspita Dian Agustina (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to describe the design, utilization, inhibiting and supporting factors, and solutions to obstacles in the use of instructional media in drama text teaching at State Senior High School 1 Tilango. This study used a descriptive qualitative approach. The research data sources were obtained from the learning process, Indonesian language teachers, and 11th-grade students. Data collection techniques were conducted through observation, interviews, and documentation, while data analysis was conducted through data reduction, data presentation, and drawing conclusions. The results of the study indicate that (1) teachers have systematically designed instructional media by preparing Lesson Implementation Plan stailored to learning objectives, material characteristics, and student needs. The designed media include PowerPoint, drama videos, Mentimeter, and KARTIKA cards; (2) the use of instructional media is varied and integrated at each learning stage, helping students understand the content and language of drama texts more easily, increasing learning motivation, and encouraging active learning; (3) inhibiting factors in the use of instructional media include students’ lack of concentration and limited internet access, while supporting factors include teacher readiness, device availability, and student enthusiasm. (4) Solutions to these obstacles are implemented through monitoring the use of digital devices, providing alternative learning options when internet access is limited, mentoring students in the use of digital media, and gradually and routinely encouraging students to use media.